Dysregulated lipid metabolism in lymphangioleiomyomatosis pathogenesis as a paradigm of chronic lung diseases - Bernardelli, Clara; Caretti, Anna; Lesma, Elena (Frontiers in Medicine, 2023)
A chronic inflammatory condition characterizes various lung diseases. Interestingly, a great contribution to inflammation is made by altered lipids metabolism, that can be caused by the deregulation of the mammalian target of rapamycin complex-1 (mTORC1) activity. There is evidence that one of mTOR downstream effectors, the sterol regulatory element-binding protein (SREBP), regulates the transcription of enzymes involved in the de novo fatty acid synthesis. Given its central role in cell metabolism, mTOR is involved in several biological processes. Among those, mTOR is a driver of senescence, a process that might contribute to the establishment of chronic lung disease because the characteristic irreversible inhibition of cell proliferation, associated to the acquisition of a pro-inflammatory senescence-associated secretory phenotype (SASP) supports the loss of lung parenchyma. The deregulation of mTORC1 is a hallmark of lymphangioleiomyomatosis (LAM), a rare pulmonary disease predominantly affecting women which causes cystic remodeling of the lung and progressive loss of lung function. LAM cells have senescent features and secrete SASP components, such as growth factors and pro-inflammatory molecules, like cancer cells. Using LAM as a paradigm of chronic and metastatic lung disease, here we review the published data that point out the role of dysregulated lipid metabolism in LAM pathogenesis. We will discuss lipids’ role in the development and progression of the disease, to hypothesize novel LAM biomarkers and to propose the pharmacological regulation of lipids metabolism as an innovative approach for the treatment of the disease.